MRI defaecography in patients with faecal incontinence. (March 2015) - Melchior, C.; Bridoux, V.; Touchais, O.; Savoye‐Collet, C.; Leroi, A.‐M.
Abstract Aim Faecal incontinence (FI) requires careful assessment of its aetiology to determine the most effective treatment. The aims of this study were to evaluate MRI defaecography in FI and to compare it with clinical examination combined with rigid rectoscopy in assessing the pelvic floor in patients with FI. Method Consecutive patients with FI referred over a 3‐year period to our tertiary centre for MRI defaecography were retrospectively studied. MRI images of the pelvic floor were compared with clinical examination and anuscopy and rectoscopy. Results Seventy‐four female patients [mean age 60.5 (30.0–81.0) years] were recruited. MRI defaecography showed conditions which often overlapped, including internal intussusception in 19 (25.7%) and pelvic floor descent in 24 (32.4%). There was average agreement between MRI and clinical examination for a significant anterior rectocoele (κ = 0.40) and poor agreement between MRI and anuscopy/rectoscopy for intra‐rectal (κ = 0.06) and intra‐anal intussusception (κ = 0.11). Conclusion Other than for anterior rectocoele, there is poor correlation between MRI defaecography and clinical examination with rigid rectoscopy. MRI can detect a variety of abnormal static and dynamic pelvic disorders. This includes enterocoele, which could result in a modification of the surgical approach to intussusception and anterior rectocoele.